The N-end rule pathway promotes seed germination and establishment through removal of ABA sensitivity in Arabidopsis - Holman, Tara J. (National Academy of Sciences, 2009)
The N-end rule pathway targets protein degradation through the identity of the amino-terminal residue of specific protein substrates. Two components of this pathway in Arabidopsis thaliana, PROTEOLYSIS6 (PRT6) and arginyl-tRNA:protein arginyltransferase (ATE), were shown to regulate seed after-ripening, seedling sugar sensitivity, seedling lipid breakdown, and abscisic acid (ABA) sensitivity of germination. Sensitivity of prt6 mutant seeds to ABA inhibition of endosperm rupture reduced with after-ripening time, suggesting that seeds display a previously undescribed window of sensitivity to ABA. Reduced root growth of prt6 alleles and the ate1 ate2 double mutant was rescued by exogenous sucrose, and the breakdown of lipid bodies and seed-derived triacylglycerol was impaired in mutant seedlings, implicating the N-end rule pathway in control of seed oil mobilization. Epistasis analysis indicated that PRT6 control of germination and establishment, as exemplified by ABA and sugar sensitivity, as well as storage oil mobilization, occurs at least in part via transcription factors ABI3 and ABI5. The N-end rule pathway of protein turnover is therefore postulated to inactivate as-yet unidentified key component(s) of ABA signaling to influence the seed-to-seedling transition.